1999
DOI: 10.1073/pnas.96.24.13750
|View full text |Cite
|
Sign up to set email alerts
|

From calcium blips to calcium puffs: Theoretical analysis of the requirements for interchannel communication

Abstract: In the cytoplasm of cells of different types, discrete clusters of inositol 1,4,5-trisphosphate-sensitive Ca 2؉ channels generate Ca 2؉ signals of graded size, ranging from blips, which involve the opening of only one channel, to moderately larger puffs, which result from the concerted opening of a few channels in the same cluster. These channel clusters are of unknown size or geometrical characteristics. The aim of this study was to estimate the number of channels and the interchannel distance within such a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
185
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(199 citation statements)
references
References 30 publications
12
185
2
Order By: Relevance
“…The number of receptors in a cluster has not been measured yet. We employ N = 25 following recent estimates by Swillens and Dupont [7]. The probability distributions p(n 3 + n 4 ) with h = 4 and p(n 3 ) with h = 3 are depicted in figure 8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of receptors in a cluster has not been measured yet. We employ N = 25 following recent estimates by Swillens and Dupont [7]. The probability distributions p(n 3 + n 4 ) with h = 4 and p(n 3 ) with h = 3 are depicted in figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…This region is usually not connected. However, Swillens et al showed that the spatial arrangement of IP 3 R channels does not influence the Ca 2+ dynamics at an open cluster [7]. Therefore, we map the area of all conducting release channels to an area of the same size concentric to the cluster area.…”
Section: Ca 2+ Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This small size of a cluster allows us to assume that the Ca 2ϩ is constant within the cluster (see also ref. 17). This in turn allows us to model the Ca 2ϩ flux from the ER into the cytosol as a point source with a weight factor that describes the strengths (size) of the source.…”
Section: Model For Intracellular Ca 2؉ Responsementioning
confidence: 99%
“…They are involved, e.g., in the stimulus-induced contraction in smooth muscle cells (11), in the hormone-induced glucose production in liver cells (12), and for the early response to injury of brain tissue (13) and corneal epithelia (14). Recent new insights into the biophysical mechanism of intracellular Ca 2ϩ release have revealed that the actual release sites are discrete and as small as Ϸ100-200 nm comprising only 20-50 release channels (15)(16)(17). The clustering of these channels is well documented in various cell types and may be a universal feature of the Ca 2ϩ release mechanism.…”
mentioning
confidence: 99%